A High-resolution Far-infrared Survey to Probe Black Hole–Galaxy Co-evolution - Matteo Bonato; David Leisawitz; Gianfranco De Zotti; Laura Sommovigo; Irene Shivaei; C. Megan Urry; Duncan Farrah; Locke Spencer; Berke V. Ricketti; Hannah Rana; Susanne Aalto; David B. Sanders; et al. (The Astrophysical Journal)
Far-infrared (FIR) surveys are critical to probing the co-evolution of black holes and galaxies, since of the order of half the light from accreting black holes and active star formation is emitted in the rest-frame IR over 0.5 ≲ z ≲ 10. For deep fields with areas of 1 deg ^2 or less, like the legacy surveys GOODS, COSMOS, and CANDELS, source crowding means that subarcsecond resolution is essential. In this paper, we show with a simulation of the FIR sky that observations made with a small telescope (2 m) at low angular resolution preferentially detect the brightest galaxies, and we demonstrate the scientific value of a space mission that would offer subarcsecond resolution. We envisage a facility that would provide high-resolution imaging and spectroscopy over the wavelength range 25–400 μ m, and we present predictions for an extragalactic survey covering 0.5 deg ^2 . Such a survey is expected to detect tens of thousands of star-forming galaxies and thousands of active galactic nuclei (AGNs), in multiple FIR lines (e.g., [C ii ], [O i ], and [C i ]) and continuum. At the longest wavelengths (200–400 μ m), it would probe beyond the Epoch of Reionization, up to z ∼ 7–8. A combination of spectral resolution, line sensitivity, and broad spectral coverage would allow us to learn about the physical conditions (temperature, density, and metallicity) characterizing the interstellar medium of galaxies over the past ∼12 billion years and to investigate galaxy–AGN co-evolution.